FUNCTION ESTIMTING THE COSTS IN DIYALA PROVINCE - Mahmood, Mhanaa A.; Jbara, Osamah K. (Diyala Agricultural Sciences Journal, 2016)
Targeted search function estimating the cost of production broiler ,in order to achive this goal were sufficient data by a random sample , and collected at random from a breeder broiler meat in Diyala whereas a total of 77 field from total of 358 as arate of 21%.When costs analysis, shows that the fact the feed content from 66.9% from changer costs , while rent from 58.88% constant cost and small field 1-15 thousands endure greater than the average of the total cost comparison from another costs .When estimating function costs was model cubic, shows that it was more appropriate, for relation in studying and harming economic , statistical and studied tests , where the function was significant at the level of 1% and 91% from total change caused by changes in total cost for broiler .The size of production optimization was 42.9 tan of number of broiler optimize was 26.01 thousand broiler and they are theoretic all superior for achievement on level sample . production is subject to increasing yield in two categories first and second , and on categories in the third category. show through economic analysis that the level of maximum potential for profit was 45.6 ton and less price can be accepted producer was 2.2 thousand diner . Through the findings of the researcher recommends that research necessary expand investment projects broiler with large sizes for production where is investment in breading broiler stay suboptimal and it is one alfrus good investment return